2015
DOI: 10.1161/circheartfailure.114.001551
|View full text |Cite
|
Sign up to set email alerts
|

Central Cardiac Limit to Aerobic Capacity in Patients With Exertional Pulmonary Venous Hypertension

Abstract: Background The mechanism of functional limitation in heart failure with preserved ejection fraction (HFpEF) remains controversial. We examined the contributions of central cardiac and peripheral mechanisms and hypothesized that the pulmonary vascular response to exercise is an important determinant of aerobic capacity among patients with exertional pulmonary venous hypertension (ePVH). Methods and Results We compared 31 ePVH patients (peak VO2<80% predicted and peak pulmonary arterial wedge pressure≥20 mmHg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
68
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 41 publications
4
68
0
4
Order By: Relevance
“…Importantly, their patients' resting PCW was elevated and increased during exercise along with the pulmonary artery pressure. Consistent with the study by Santos et al, 4 the reduction in VO 2 in patients with HFpEF was because of an inadequate increase in cardiac output, attributable to both lower stroke volume and heart rate at peak exercise. There was no difference in peak CaO 2 −CvO 2 .…”
Section: Articles See P 278 and P 286supporting
confidence: 87%
See 2 more Smart Citations
“…Importantly, their patients' resting PCW was elevated and increased during exercise along with the pulmonary artery pressure. Consistent with the study by Santos et al, 4 the reduction in VO 2 in patients with HFpEF was because of an inadequate increase in cardiac output, attributable to both lower stroke volume and heart rate at peak exercise. There was no difference in peak CaO 2 −CvO 2 .…”
Section: Articles See P 278 and P 286supporting
confidence: 87%
“…4,5 Both groups performed upright cardiopulmonary exercise testing with hemodynamic monitoring in patients with preserved ejection fraction, elevated pulmonary capillary wedge pressure (PCW), and exercise intolerance. Santos et al 4 found that the major contributor to exercise disability was a limitation of cardiac output, indicating a cardiac cause.…”
Section: Articles See P 278 and P 286mentioning
confidence: 99%
See 1 more Smart Citation
“…Santos et al 11 and Abudiab et al 12 suggested that the major contributor to exercise inability in HFpEF patients is the reduced cardiac output relative to metabolic needs, indicating a cardiac cause. Extensive fibrosis and titin hypophosphorylation 7 is thought to create stiffness in the LV of patients with HFpEF, contributing to the cardiac limitations in exercise capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Most recent studies, especially performed in subjects with HF and preserved ejection fraction, have definitively changed this paradigm by looking at the variety of complex mechanisms that limit the oxygen (O 2 ) transport chain from air to mithocondria [5][6][7] and, through this, discerning how the physical therapeutic approach may work. 8 According to the Fick principle, VO 2 depends on cardiac output (CO) times O 2 artero-venous difference (A-VO 2 diff) and reflects the product of the integrated biological response of the heart and peripheral mechanisms involved in O 2 delivery (convection), diffusion and extraction during exercise.…”
mentioning
confidence: 99%